Nursing of four patients with acute pancreatitis after lower extremity endovascular intervention (4例下肢血管腔内治疗术后并发急性胰腺炎的护理体会) - FANG Xiaomei (方晓梅); LIU Huanping (刘焕萍); WANG Ting (王婷) (中西医结合护理)
This paper summarized the nursing measures for four patients with acute pancreatitis after lower extremity endovascular intervention, and provided a reference for the postoperative nursing of vascular intervention surgery. Key issues of nursing included psychological care, preoperative hydration, guidance of dietary, observation of illness condition, prevention of complications, nutrition support and medication care. There are two severe cases of acute pancreatitis, one of which eventually died due to multiple organ failure, and the other was cured after drug treatment. In addition, two mild cases of acute pancreatitis, which were cured after drug treatment. As rare angiographic complication, acute pancreatitis is not easy to be detected early. The possibility of acute pancreatitis must be considered when a patient presents with abdominal pain, elevated creatinine, or multiple organ failure following an interventional procedure. Early detection and diagnosis, and timely treatment are beneficial to improve the cure rate of postoperative complications. (本文总结4例下肢血管腔内治疗术后并发急性胰腺炎患者的护理体会, 为介入术后的精细化护理提供参考。护理要点包括: 实施心理护理, 给予术前合理水化、饮食指导, 加强病情观察, 积极预防并发症发生, 提供营养支持, 完善用药护理。2例重症急性胰腺炎患者中, 1例最终因多脏器功能衰竭死亡, 另1例转入ICU治疗后出院; 2例轻症急性胰腺炎患者经药物治疗后痊愈。腔内治疗术后并发急性胰腺炎是一种罕见的血管造影并发症, 不易早期发现, 当患者在介入手术后出现腹痛、肌酐升高或多器官衰竭时, 必须考虑急性胰腺炎的可能性, 做到早发现、早诊断、早治疗, 有利于提高术后并发症的治愈率。)